Effects of igneous intrusions on coalbed methane potential, Gunnedah Basin, Australia - Gurba, Lila W; Weber, Carl R (International journal of coal geology, 2001)
The Gunnedah Basin, NSW, Australia, contains more than 500 Gt of coal, and has been the subject of recent coalbed methane exploration. Large areas of the basin contain igneous intrusions and large areas of coal have been heat-affected as a consequence. A detailed study has been undertaken of coal seams intersected in a cored coalbed methane exploration drillhole in which two sill-form igneous intrusions are present. Comparisons are made between coals that are unaltered and coals that have been heat-affected, using petrographic and chemical data, coal seam gas desorption data, and gas chemical analysis data. Results demonstrate that the two igneous intrusions have had a very positive effect on coalbed methane development. The gas content in a number of heat-affected coal seams within thermal aureoles above and below the sills is substantially higher than in adjacent unaffected coal seams. In addition, the intrusions have had little effect on gas quality. The coals in the heat-affected zone were found to contain gas with approximately 95% methane. The coals in the thermal aureoles were found, under the microscope, to contain characteristic micropores and slits, which collectively may serve to enhance gas adsorption capacity, permeability, and gas desorption. Gas contents below each of the sills is substantially higher than above the sill, confirming earlier results that the sills appear to have acted as a reservoir seal, during and for some time after intrusion. The background coal rank in ACM Yannergee DDH 1 is in the high-volatile bituminous range. The igneous intrusions have resulted in an increase in rank such that large areas of coal have moved into the optimal thermogenic gas generation window. This rank increase has affected a major part of the coal-bearing sequence.